Taking Stock: Perspectives on British Urban History - Rodger, Richard (Urban History Review / Revue d'histoire urbaine, 2003)
Drawing on an unprecedented volume of recent scholarship on the urban history of Britain, this paper seeks to identify areas for future academic research. These include a closer alignment of intellectual disciplines to cross-fertilise approaches to the historical study of towns and cities; a more resolute engagement by urban historians with audio and visual sources and a generally more coherent archival policy for the contemporary period; further integration of Irish perspectives into the study of British urban history; and a more imaginative analytical framework than town typologies by which to understand the process of urban change. In addition, a number of other areas are suggested, and the article concludes on a positivist note by reflecting on the extent to which the field of British urban history has been consolidated and rendered accessible to specialist historians and general public alike.